Autosomal and Mitochondrial Adaptation Following Admixture: A Case Study on the Honeybees of Reunion Island. (29th November 2017) - Wragg, David; Techer, Maéva Angélique; Canale-Tabet, Kamila; Basso, Benjamin; Bidanel, Jean-Pierre; Labarthe, Emmanuelle; Bouchez, Olivier; Le Conte, Yves; Clémencet, Johanna; Delatte, Hélène; Vignal, Alain
Abstract: The honeybee population of the tropical Reunion Island is a genetic admixture of the Apis mellifera unicolor subspecies, originally described in Madagascar, and of European subspecies, mainly A. m. carnica and A. m. ligustica, regularly imported to the island since the late 19th century. We took advantage of this population to study genetic admixing of the tropical-adapted indigenous and temperate-adapted European genetic backgrounds. Whole genome sequencing of 30 workers and 6 males from Reunion, compared with samples from Europe, Madagascar, Mauritius, Rodrigues, and the Seychelles, revealed the Reunion honeybee population to be composed on an average of 53.2 ± 5.9% A. m. unicolor nuclear genomic background, the rest being mainly composed of A. m. carnica and to a lesser extent A. m. ligustica . In striking contrast to this, only 1 out of the 36 honeybees from Reunion had a mitochondrial genome of European origin, suggesting selection has favored the A. m. unicolor mitotype, which is possibly better adapted to the island's bioclimate. Local ancestry was determined along the chromosomes for all Reunion samples, and a test for preferential selection for the A. m. unicolor or European background revealed 15 regions significantly associated with the A. m. unicolor lineage and 9 regions with the European lineage. Our results provide insights into the long-term consequences of introducing exotic specimen on the nuclear and mitochondrial genomes of locally adapted populations.